Comparing Drug Addiction Portrayed in Hubert Selby Jr’s Requiem for a Dream and Irvine Welsh’s Trainspotting - Cindy Dwi Andary (Talenta Publisher, 2023)
This article aims to compare two literary works from two different countries with a similar motif, which is drug addiction. This study attempts to find out the portrayal of drug addiction in both literary works by comparing the symptoms, causes, and impacts experienced by the main characters. Based on the results of the analysis, it can be concluded that the two literary works show similarities and differences regarding drug addiction that happen to the main characters. The writer found four symptoms, one cause, and four impacts of drug addiction in Requiem for a Dream, while in Trainspotting, the writer found three symptoms, two causes, and four impacts of drug addiction. Despite having the same number of impacts, those four impacts are described differently in both literary works.